Introducing the new nutrition guideline to Indonesian overweight/obese adolescents using a short movie: the impact on nutritional knowledge, eating habit and dietary intake - Marliya, Marliya; Luglio Muhammad, Harry Freitag (Progress in Nutrition, 2019)
Background: Overweight and obesity were associated with increased energy intake therefore an effective approach to prevent the excess intake of energy is warranted. The Indonesian Ministry of Health has recently published the new nutrition guideline that aimed to improve dietary practice and to reduce nutrition related problems. Objective: The aim of this study was to examine the effect of an educational movie on nutritional knowledge, eating habit and dietary intake in overweight/obese adolescents.  Method: A total of 80 overweight/obesity subjects aged 15 to 17 years old participated in this study. Those subjects were divided into two groups: control group (lecture only) and movie group (lecture + movie). Nutritional knowledge, eating habit and dietary intake were measured before and after the intervention. Result: Both groups had increment in nutritional knowledge after the intervention but movie group had higher increment than those in control group (p